FACTORS INFLUENCING THE EFFECTIVENESS OF ENGLISH READING CLASSROOM MANAGEMENT AT THE EIGHTH GRADE OF UPTD SMP NEGERI 1 GUNUNGSITOLI BARAT - Sendi Cahaya Cerah Zebua, Six; Telaumbanua, Yasminar Amaerita; Harefa , Afore Tahir; Laoli , Adieli (FKIP Unismuh Makassar, 2024)
Classroom management competencies have a major impact on student learning and academic achievement. The main aspects that need to be evaluated in this classroom management effectiveness setting include the teacher's role, the classroom environment and student characteristics. First, the teacher's role in classroom management has an impact on its effectiveness. Teachers with strong classroom management skills usually produce a positive, disciplined and structured learning environment. Conversely, a teacher's failure to control the classroom can result in learning disruptions, demotivated students and difficulty achieving learning objectives. Classroom management is an important part of optimizing the role and potential of educators in learning. The key to successful learning is improving the quality of student learning. This study aims to describe the realization of classroom management by English teachers and find out what the factors are that influence the effectiveness of classroom management in learning English reading, especially in class VIII-B at UPTD SMP Negeri 1 Gunungsitoli Barat. The method used in this research is qualitative research with an inductive approach. Data were obtained through observations and interviews with English teacher. Data from the observation sheet was analyzed to find out the indicators that have been implemented by English teachers in managing the classroom in learning to read English. Meanwhile, the interview data was analyzed to find out what the factors are that influence the effectiveness of classroom management in learning to read English. The results showed that English teacher have Classroom management was realized, although it has yet to be fully deployed. The following aspects influence the success of classroom management in learning to read English: information about student needs, time management, and teacher experience.